STUDY THE PRODUCTION AND CONTROL SYSTEM OF HYDROPOWER NAMKHAN 3 - SAYPASERTH , Phetsadachanch; VAR, Somchan (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
Now, a country that has many developers to build hydroelectric power plants due to energy use, electricity generation, power sources, more important sources to meet the need to use power to produce electricity. Hydroelectric power dam is the source of the main electrical power of electricity generation, decentralization to various users such as: communications and industrial technology business. Minister broader said. Electricity has become an important factor in the livelihood and development of the country, especially when the demand for electricity increases. Every generation of electricity from the source to load There fore, the demand for electricity increases. Through a study of the production and control systems of the Nam Khan 3 power plant, Xieng Ngeun district, Luang Prabang province, can be summarized as follows: Table 1 Calculation of reservoir area, installation of the Nam Khan 3 power. No Content of information Facts Data Computed data 1 Reservoir Area Nam Khan 3 power 9.21 km2 9.086 km2 2 Installing of Nam Khan 3 power 30 MW 29.743 MW Table 2 summarizes the electricity output of the Nam Khan 3 hydropower plants for the year 2018. Month Production power Calculated as% against plan Plan(kWh) Action(kWh) Jan 14,880,000 10, 525,000 70.73 Feb 10,080,000 8,352,500 82.86 Mar 11,160,000 10,095,000 90.46 Apr 10,800,000 8,675,000 80.32 May 10,230,000 8,067,500 78.86 Jun 14,400,000 16,612,500 115.36 Jul 22,320,000 22,450,000 100.58 Aug 21,600,000 7,540,000 34.91 Sep 22,320,000 7,962,500 35.67 Oct 28,272,000 17,242,500 60.99 Nov 17,280,000 25,157,500 145.59 Dec 13,392,000 16,342,500 122.03 Based on empirical studies and calculations, it is found that there is relatively little value from the actual analysis in the Nam Khan 3 Hydroelectric Power.